Controversies in Political Ideologies: A Critical Discourse Analysis of Speeches of Indian and Pakistani Premiers on Pulwama Incident - Muhammad Imran Shah; Saeed Ahmad Ahmad; Ali Danishs (UIN Salatiga, 2021)
Critical Discourse Analysis (CDA) is considered an effective approach to exploring a text's hidden realities. The current research analyzes the speeches of the leaders of the two states on the incident of Pulwama attack on 14th February 2019 in the region of Indian occupied Kashmir to control the minds of the audience and formulate their ideologies to achieve their political benefits through power abuse. The data has been taken from the speeches delivered by both political leaders, the Premier of Pakistan Imran Khan and the Premier of India, Narendra Modi, on Pulwama Attack. Both qualitative and quantitative research approaches have been followed to investigate the texts. For Quantitative data, AntConc 3.5.8 has been utilized for the frequencies and concordance of the important words to be discussed. Observation has been utilized to gain in-depth information to describe qualitatively. The results show that some specific linguistic choices regarding some particular vocabulary, pronouns, and modal verbs have been used ideologically by the premiers to manipulate the language of their speeches. The study will be important for researchers who want to investigate the discourse developed by the political leaders’ speeches on the same issue.Keywords: discourse; pronoun; modality corpus; intertextuality